THE INFLUENCE OF INDEPENDENCE RATIO AND EFFECTIVENESS RATIO ON ECONOMIC GROWTH THROUGH CAPITAL EXPENDITURE - Ni Made Santi Dewi Pradnyani; Ni Putu Santi Suryantini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Indonesia's economic growth over the last few years has experienced quite significant fluctuations. The large economic growth rate cannot be separated from the large influence of regional income for each province in Indonesia, one of which is Bali Province. This research aims to determine the effect of the independence ratio and effectiveness ratio on economic growth through capital expenditure in districts/cities in Bali Province for the 2018-2022 period. This research method uses an associative type of quantitative research. The data in this research is secondary data, consisting of data on economic growth, independence ratio, effectiveness ratio, and capital expenditure with the population of all Regencies/Cities of Bali Province. The data analysis technique in this research uses panel data regression using EViews version 10.0 because EViews has special capabilities for processing panel data, namely data that combines cross-section and time series data. The research results show thatthe independence ratio has a significant positive effect on capital expenditure, the effectiveness ratio has a significant negative effect on capital expenditure, the independence ratio has an insignificant negative effect on economic growth, the effectiveness ratio and capital expenditure have a significant positive effect on economic growth, while capital expenditure is unable to mediate the effect of the independence ratio and ratio of effectiveness to economic growth. This research contributes to local governments in districts/cities in Bali Province in designing effective and sustainable economic development policies.